Intensification of load flexible fixed bed reactors by optimal design of staged reactor setups - Fischer, Konrad; Freund, Hannsjörg (Chemical Engineering and Processing, 2020)
The dynamic and load flexible operation of fixed bed reactors has recently gained considerable interest for processes where large fluctuations of the feed flow rate are expected. Load flexibility poses new challenges regarding the reactor design and operation in comparison to the conventional steady state operating mode. These challenges can be managed by a more conservative reactor design, but it creates a performance gap between conventional and load flexible reactors. The intensification of load flexible wall-cooled fixed bed reactors is approached using the methanation of carbon dioxide as case study. An optimization problem is formulated which bases on the simultaneous optimization of the reactor design and several steady state operating points within a desired load range. The identified staged reactor setup with a catalyst dilution profile tolerates large variations of the flow rate up to 80 % and shows a significant improvement of the load flexible reactor performance. A considerable potential of a split and bypass of the feed stream to other stages is identified, which enables an adaption of the axial flow field according to the current load level. The feasibility of the identified setup for the dynamic operation is successfully verified by dynamic simulation of different operating scenarios.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Carbon dioxide methanation; Catalyst dilution profile; Dynamic operation; Feed distribution; Model-based reactor optimization; Wall-cooled tubular reactor

On the optimal design of load flexible fixed bed reactors: Integration of dynamics into the design problem - Fischer, Konrad; Freund, Hannsjörg (Chemical Engineering Journal, 2020)
The design of dynamically operated fixed bed reactors is a challenging task, especially for highly exothermic reactions. Fluctuations of process conditions such as inlet flow rate and composition can cause losses in product quality, wrong-way behavior or even a thermal runaway which damages reactor and catalyst. We present a methodology for the model-based design of dynamically operated, load flexible fixed bed reactors. Critical reactor dynamics are already considered during the reactor design and are integrated into the optimization problem. Instead of a steady state problem, the reactor is optimized for a worst case dynamic scenario. The optimization approach yields a design which allows for safe transitions from any flow rate to another within a pre-defined load range. The approach is introduced using the methanation of carbon dioxide as an important case study of high relevance for both research and society within the context of chemical energy storage of fluctuating renewable energy. A feasibility test demonstrates the safe reactor operation for a time horizon which includes a series of step-changes of the inlet flow rate as an approximation of a fluctuating hydrogen supply.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Carbon dioxide methanation; Dynamic operation; Model-based reactor optimization; Thermal runaway; Wall-cooled tubular reactor; Wrong-way behavior